(untitled) (Global Journal of Human-Social Science, 2020)
Human Resource is the key to the success of any nation. Without women literacy and empowerment, Human Resource development of a nation cannot achieve its goals. Hence women literacy as well as empowerment is equally important. For sustainable development of the Indian economy, women empowerments are highly prioritized. According to the census of 2011, women constitute 48.2% of the total population of India. Though many women of our country are empowering themselves, but still there are some Muslim women of our country who remain backward in education and development. Muslim women always remained socially and economically backward in our country. Their low participation in education becomes a barrier in the path of achieving the goal of universal education. Even within the context of education in general, there is a wide gap between the Muslim women and the women belonging to other religions and communities. The problems of the Muslim women are much different and more complex than their counterparts belonging to other religions. Indian Muslims women are far behind in achieving the literacy status because of their poor economic conditions and patriarchy society, religious superstitions.